Systematic Literature Review: The Role of Academic Buoyancy on Academic Achievement in High School Students and Its Implications for Guidance and Counseling - Muhammad Nur Habibi; Ahman; Sunarya, Yaya; Ferianti (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Currently, a new study is needed that can provide benefits related to improving the quality of education. As an effort to improve the quality of education in high schools, there is an interest in studying the role of academic buoyancy in one of the basic goals that school students want to achieve, namely academic achievement. Academic buoyancy is the ability to survive and succeed in facing daily academic difficulties at school so that it is expected to have an effect on improving academic achievement. This study aims to analyze the role of academic buoyancy on the academic achievement of high school students, and to explain the implications of the results of this study for guidance and counseling. This study uses a systematic literature review method. Data collection was carried out using the PRISMA (Protocol Review Systematic and Meta-Analysis) statement method, with the help of the Harzing's Publish or Perish application on the Scopus database. The results of the study indicate that academic buoyancy has a positive effect on academic achievement, both directly, as a mediator of other variables, and as an indirect effect on academic achievement. The implications of the results of the study for guidance and counseling are discussed further in the discussion section.